The dissipation and degradation of methoxy‐ 14C malathion in soil under tropical conditions - Getenga, Zachary; Jondiko, J.I.O.; Wandiga, S.O. (Taylor & Francis Group, 2000)
l4C-malathion[S-1,2-bis(ethoxycarbonyl) ethyl O,O-dimethyl phosphorodithioate] has been studied in soil under tropical field conditions by applying the 14C-malathion pesticide to soil in Polyvinyl chloride (PVC) pipes and monitoring it with elapsed time. In one area, 14C-malathion dissipated with a half-life values of 36.7 days and 41 days in the long rain and short rain seasons respectively. The bound residue of malathion in the soil built up to 51.8% and 73.4% of the initial pesticide dose in the short and long rain seasons, respectively. However, after sometime the bound residue decreased and this has been attributed to biodegradation by micro-organisms in the soil. In another area, 14C-malathion dissipated slowly with a half-life value of 770 days in the dry spell. The bound residue built up in the soil slowly, attaining a value of 5.49 μg/g (35.4%) of the initial pesticide dose after 70 days. The bound residues did not decrease at some stage and this has been attributed to the prevailing dry conditions, which did not promote the biodegradation of the bound residues in the soil by micro-organisms. The metabolites in the soil as determined by TLC and confirmed by GC-MS, showed the presence of malaoxon and the malathion o-mono or β-mono carboxylic acid in addition to the parent compound, malathion.
Keywords: 14C-malathion; half-life under field conditions